Association between adiposity after diagnosis of prostate cancer and mortality: systematic review and meta-analysis - Margarita Cariolou; David C Muller; Dagfinn Aune; Konstantinos K Tsilidis; Georgios Markozannes; Nerea Becerra-Tomás; Rita Vieira; Katia Balducci; Doris S M Chan (BMJ Medicine)
Objective To explore the associations between adiposity indices, assessed at or after a diagnosis of prostate cancer, and mortality.Design Systematic review and meta-analysis.Data sources PubMed and Embase, from inception to 16 November 2022.Eligibility criteria for selecting studies Cohort studies or randomised controlled trials of men with a diagnosis of prostate cancer that investigated the associations between adiposity (body mass index, waist and hip circumference, waist-to-hip ratio, and subcutaneous and visceral adipose tissue) after diagnosis and mortality outcomes. A modified version of the risk of bias for nutrition observational studies tool was used to assess risk of bias.Results 79 studies were identified that investigated adiposity indices after a diagnosis of prostate cancer in relation to mortality. No randomised controlled trials were found. A non-linear dose-response meta-analysis indicated a J shaped association between body mass index and all cause mortality (33 910 men, 11 095 deaths, 17 studies). The highest rate of all cause mortality was found at the lowest and upper range of the distribution: 11-23% higher rate for a body mass index of 17-21 and 4-43% higher rate for a body mass index of 30-40. The association between body mass index and mortality specific to prostate cancer was flat until body mass index reached 26-27, and then increased linearly by 8-66% for a body mass index of 30-40 (33 137 men, 2947 deaths, 13 studies), but the 95% confidence intervals were wide. These associations did not differ in most predefined subgroups by study design, number of deaths, anthropometric assessment, follow-up time, geographical location, prostate cancer risk group, and adjustment variables. No associations were found in meta-analyses between 10 cm increases in waist circumference and all cause mortality or mortality specific to prostate cancer, but only three studies were available. The few studies with data on change in weight, waist-to-hip ratio, and subcutaneous and visceral adipose tissue reported conflicting results.Conclusions This review suggests that patients with prostate cancer might benefit from maintaining a healthy weight and avoiding obesity. Future studies should investigate adiposity across different stages of cancer survivorship and use various parameters for distribution of adipose tissue.Systematic review registration Open Science Framework https://osf.io/qp3c4.